Peran Eksekutif Konsuler Dalam Mewujudkan Itikad Baik Negara Pengirim: Kajian Kasus Diah Ayu Kurniasari Terhadap Efektivitas Pasal 5 Konvensi Wina 1963 Bagi Diaspora Indonesia - Yolanda Febriani; Ridho Saputra; Wahyu Ageng Rizky Dian Pradana (GLOBAL SCIENTS PUBLISHER, 2026)
This study analyzes the effectiveness of the consular executive function in providing protection to Indonesian citizens abroad, focusing on the case of Diah Ayu Kurniasari, who faces the death penalty in Malaysia. Using a normative juridical approach and case study, this study examines the implementation of Article 5 of the 1963 Vienna Convention on Consular Relations in the context of the good faith of the sending state. The findings indicate that although the 1963 Vienna Convention provides a comprehensive legal framework, the effectiveness of consular protection depends heavily on institutional capacity, inter-agency coordination, and the political commitment of the sending state. The case reveals structural and operational challenges, including limited access, the complexity of receiving state law, and sensitive diplomatic dimensions. This study recommends strengthening consular capacity, improving inter-ministerial coordination, and developing rapid response mechanisms for critical cases involving Indonesian citizens abroad.